Narative and Dramatics of Psalm 73: Orientation, Disorientation and Reorganization - Beck, Boris; Berković, Danijel (Anafora, 2023)
Psalm 73 occupies a central position in the biblical Psalter, not only physically but also with regard to the subject of the suffering of the just, and the question it poses  of an absent God who allows the evil to prosper - is repeated in many places of Scripture. The psalmist experiences an inner drama of doubt and reinforcement of faith in the psalm, and the dramatic structure of the text is linked to the stages of the religious crisis of the psalmist. The psalmist goes from a reliable orientation towards God to disorientation and ends in reorientation. Each of these phases is associated with the changing of the dramatic situation and time period, and the theology and narrative of Psalm 73 are inseparably linked and necessarily illuminate one another. At the outset of the psalm, the psalmist departs from the biblical view of the world's order, falls into the abyss of suspicion which he perceives as animalization, and ultimately returns to the inspired position of faith from which he started. In the text, the psalmist has revealed his confession and prophecy for others, to be a model and a guide to the readers or listeners on their own spiritual journey - to help as an individual to establish faith in the community.